RNA folding and functions of RNA helicases in ribosome biogenesis. Issue 1 (31st December 2022) - Mitterer, Valentin; Pertschy, Brigitte
ABSTRACT: Eukaryotic ribosome biogenesis involves the synthesis of ribosomal RNA (rRNA) and its stepwise folding into the unique structure present in mature ribosomes. rRNA folding starts already co-transcriptionally in the nucleolus and continues when pre-ribosomal particles further maturate in the nucleolus and upon their transit to the nucleoplasm and cytoplasm. While the approximate order of folding of rRNA subdomains is known, especially from cryo-EM structures of pre-ribosomal particles, the actual mechanisms of rRNA folding are less well understood. Both small nucleolar RNAs (snoRNAs) and proteins have been implicated in rRNA folding. snoRNAs hybridize to precursor rRNAs (pre-rRNAs) and thereby prevent premature folding of the respective rRNA elements. Ribosomal proteins (r-proteins) and ribosome assembly factors might have a similar function by binding to rRNA elements and preventing their premature folding. Besides that, a small group of ribosome assembly factors are thought to play a more active role in rRNA folding. In particular, multiple RNA helicases participate in individual ribosome assembly steps, where they are believed to coordinate RNA folding/unfolding events or the release of proteins from the rRNA. In this review, we summarize the current knowledge on mechanisms of RNA folding and on the specific function of the individual RNA helicases involved. As the yeast Saccharomyces cerevisiae is the organism in which ribosome biogenesis and the role of RNA helicases in this process is best studied, we focused our review on insights from this model organism, but also make comparisons to other organisms where applicable.